Description of Knowledge of Unsafe Attitudes and Behaviors in Welding Workshop Workers in Kupang City - Kase, Yumri Somi; Berek, Noorce Ch.; Salmun, Johny A.R. (Faculty of Public Health, Nusa Cendana University, 2023)
Unsafe behavior (unsafe action) is a dangerous behavior that can cause a work accident that causes loss of injury to death. The purpose of this research is to describe the knowledge, attitudes and risky behavior of welders in Kupang City This research is a descriptive study with a cross-sectional design with a population of welders in the city of Kupang with a sample size of 76. The questionnaire is the research tool used. The results showed that the age group at risk showed the safest behavior (44.9%), besides that safe behavior was mostly carried out by respondents with a higher education level of 67.3% and respondents with years of service who met the requirements of 77.6%. As for unsafe behavior, the highest number of respondents with normal working duration was 70.4%, respondents with bad knowledge were 85.2% and respondents with negative work attitudes were 77.8%, while respondents with the use of complete PPE had safe behavior by 73.5%. Welding shop owners are advised to reward employees who wear PPE and offer counseling on the consequences of risky behavior as a way to raise awareness about how work accidents can affect productivity in an organization